Evaluating the Human Factor in Bank Cybersecurity: Strategies for Improving Employee Awareness and Reducing Insider Threats - Raza, Md. Adil; Hossain, Mohammad Amir; Mahjabeen, Farhana; Rahman, Jami Yaseer; Rahman, Taqi Yaseer (Indonesian Journal of Advanced Research, 2025)
The human factor proves to be a considerable weakness in the banking security infrastructure even when advanced cybersecurity technologies are being implemented by various banks. Breaches involving employees have been a huge factor in bank cybersecurity issues this research, look at the impact of employees in bank security, and how breaches have an insidious human behavior element. It notes risks like phishing attacks, negligence and intentional insider threats and heavy strategies need to respond to these risks. The research shows employing targeted awareness programs, continuous training, and behavioural analytics bases can help organizations reduce such humanrelated vulnerabilities through a combination of case studies, employee surveys and expert consultations. It also addresses the adoption of Zero Trust Architecture and continuous monitoring of activities to detect and prevent insider threats. Fostering employee awareness and building a culture of security will protect banks from both outside and inside cybersecurity threats. It helps derive actionable findings to create a resilient humancentric cybersecurity structure in the banking domain.